Meningkatkan Keterampilan Berpikir Kritis Dan Hasil Belajar Peserta Didik Menggunakan Model Bahimat Di Sekolah Dasar - Sintya Rahmawati; Aslamiah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this study’s the lack of activity, critical thinking skills, and student learning outcomes in learning mathematics. This’s cause learning activities aren’t contextual, oneway, and learning isn’t meaningful. Help to solve the problem using the BAHIMAT model (Problem Based Learning, Think Pair Share dan Index Card Match). This study aims to describe teacher activities and analyze activities, critical thinking skills and student learning outcomes. This study used qualitative approach with the type of Classroom Action Research which was carried out in 3 meetings in class IV-B SDN Mawar 2 Banjarmasin with a total of 28 students. Data collection techniques using cross tables. Data analysis is in the form of descriptive analysis. Based on the results of the study it can be concluded: (1) the teacher's activities were carried out very well at meeting 3. (2) at meeting 3 student activity increased with the criteria "Almost All Students Are Very Active", students' critical thinking skills increased with the criteria "Almost All Students Skilled”, and student learning outcomes reached 100%. As for suggestions for teachers as an alternative, for school principals as coaching, and for further researchers as a reference in using learning models that can improve the quality of teacher, student activity, critical thinking, and learning outcomes.